Implementasi Terapi Murottal Surah Ar-Rahman untuk Mengurangi Tingkat Kecemasan pada Pasien di Ruang Pre Anestesi - Priyatama, Rajendra; Susanto, Amin; Suandika, Made (Yayasan Inspirasi El Burhani, 2025)
Introduction: Surgery and anesthesia are often factors that trigger anxiety in preoperative patients. Pre-anesthesia anxiety can affect blood pressure, heart rate, and anesthesia stability during surgery. This condition affects physiological responses through activation of the amygdala and sympathetic nervous system, which reduces patient comfort. Anxiety can be managed through non-pharmacological therapies such as Surah Ar-Rahman recitation therapy, which can be used to reduce patient anxiety levels. Objective: This activity aims to apply Surah Ar-Rahman recitation therapy as a non-pharmacological intervention to reduce preoperative anxiety and increase patient comfort. Method: The implementation method involved 35 preoperative patients aged 18–75 years who were Muslim and experienced mild to moderate anxiety. Surah Ar-Rahman verses 1–78 were recited for 15 minutes using a smartphone and headphones in a quiet room. Anxiety levels were measured using the Amsterdam Preoperative Anxiety and Information Scale (APAIS) before and after therapy, and reevaluated 15 minutes before surgery. Data were analyzed descriptively by comparing the percentage change in anxiety levels before and after the intervention. Result: The results showed an increase in the proportion of patients with mild anxiety from 40% to 57.1% and a decrease in moderate anxiety from 60% to 42.9% after therapy. The average anxiety score also decreased from 15.2 to 11.8 points. Murottal therapy proved to be effective in providing relaxation, safe without causing side effects, and supporting the spiritual and emotional comfort of patients. Conclusion: In conclusion, education and murottal therapy of Surah Ar-Rahman can be a beneficial complementary intervention in preoperative anxiety management, while strengthening holistic and humanistic nursing care.